Brugada syndrome in the forensic field: what do we know to date? - Oscar Campuzano; Oscar Campuzano; Oscar Campuzano; Simone Grassi; Estefanía Martínez-Barrios; Estefanía Martínez-Barrios; Estefanía Martínez-Barrios; Andrea Greco; Andrea Greco; Andrea Greco; Vincenzo Arena; Georgia Sarquella-Brugada; et al. (Frontiers in Cardiovascular Medicine)
Brugada Syndrome is a cardiac genetic entity associated with an elevated risk of life-threatening arrhythmias, making accurate and prompt diagnosis vital to prevent lethal outcomes. To date, no macroscopic alterations have been identified in diagnosed patients, but microscopic alterations have been reported in some cases, which remain a matter of argue. This is especially relevant in the forensic field, helping to perform a post-mortem diagnose. Molecular autopsy may help to identify the genetic alteration, but other data such as family history and the situation of death are crucial to unravel the definite cause of an unexpected decease. Deleterious variants in the SCN5A gene are the most common cause of Brugada syndrome; however, the genetic diagnostic yield of Brugada Syndrome remains low, with a deleterious variant in SCN5A identified in only a 25%–30% of cases, and a high number of phenotype-positive genotype-negative individuals. This along with a proper clinical-genetic interpretation and the management of variants of unknown clinical significance remains a current challenge. Our review aims to update the available forensic data focused on autopsies performed in Brugada syndrome cases.